Information Encryption Methods to Reduce Network-on-Chip Energy Efficiency - Sharath Kumar, D.R.V.A.; Lovina, P.A. (International Journal of Psychosocial Rehabilitation, 2024)
As innovation shrinks, the energy produced by network-on-chip connections commences to compete among the energy absorbed by certain machinery of the interaction module, notably servers and web switches. In this document, we introduce a collection of information encryption systems directed at decreasing the energy wasted by the NoC connections. Dynamic energy diffusion in connections is a key contributor to NOC energy usage. This attempt uses grey coding systems to analyse the decrease in conversion behavior. Our sophisticated system may not involve any shift in devices or connection design. The prospective system utilizes the signal's binary to color transformation and the recipient's color to binary transformation. An investigational outcome showed the efficiency of the suggested systems in terms of energy dissipation and region distortion in the Web Functionality (WF) relative to information encryption